ETHICS OF SOCIAL CONSEQUENCES AND ISSUE OF THE PRINCIPLE OF HUMANITY IN MEDICAL ETHICS - Martin Gluchman; Jan Kalajtzidis (European Scientific Journal, ESJ, 2014)
Presented paper is going to introduce contemporary Slovak ethical theory, the ethics of social consequences and the principle of humanity in particular. The ethics of social consequences can be characterized as a contemporary ethical theory, along with its approach as a specific form of consequentialism. Non-utilitarian consequentialism (the position which the ethics of social consequences identifies itself with) is a relatively new form of consequentialism which began to accommodate itself only in the late 20th century. It is a form of consequentialism130 which develops from the critique of utilitarianism (classical consequentialism). This critique comes from different sources, namely from ethical theories which don’t classify themselves as consequentialist at one hand (at most times its deontology or/and ethics of virtue), but mostly from consequentialism itself.